ANALISIS PENGELOLAAN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR - Chindytia; Gede Agung, Anak Agung; Indriani, Ni Putu; Gede P. Ariyasa, I Wayan; Dwijasari, Ni Made (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the management of facilities and infrastructure in improving the quality of education at SD Negeri 2 Pejeng. This research was motivated by the importance of educational facilities and infrastructure in supporting effective and conducive learning processes. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the management of facilities and infrastructure at SD Negeri 2 Pejeng had generally been implemented well. This can be seen from the utilization of classrooms, libraries, school health units (UKS), and the maintenance of a clean and comfortable school environment. Teachers also attempted to utilize available learning media to support the learning process. However, several obstacles were still encountered, including limited school funding, inadequate technology-based learning facilities, and limited infrastructure management personnel. Despite these limitations, the school continued to optimize available facilities through collaboration among school members. Proper management of facilities and infrastructure plays an important role in supporting the improvement of educational quality in elementary schools.